Bacteriophage Therapy on an In Vitro Wound Model and Synergistic Effects in Combination with Beta-Lactam Antibiotics - Guillermo Santamaría-Corral; John Jairo Aguilera-Correa; Jaime Esteban; Meritxell García-Quintanilla (Antibiotics)
One of the primary opportunistic pathogens that can cause a wide range of diseases is Pseudomonas aeruginosa. This microorganism can become resistant to practically every antibacterial currently in use, including beta-lactam antibiotics. Its ability to proliferate as biofilm has been linked to, among other things, the failure of antimicrobial therapies. Due to a variety of virulence factors and host immune system modifications, P. aeruginosa is one of the most significant and common bacteria that colonize wounds and burns. A novel therapeutic option for treating these multidrug-resistant (MDR) bacterial infections is the combination of antibiotics and bacteriophages. This approach has been linked to improved biofilm penetration, a decreased selection of antibiotic and bacteriophage resistance, and an enhanced antibacterial impact. Combining the F1Pa bacteriophage and beta-lactam antibiotics reduced the viability of the mature biofilm of MDR P. aeruginosa strains and suppressed bacterial growth in vitro. F1Pa critically reduced the amount of biofilm that MDR P. aeruginosa clinical strains formed in the in vitro wound model. These findings highlight the bacteriophage F1Pa’s therapeutic potential as a prophylactic topical treatment against MDR pseudomonal infections in wounds and burns.